Sacra Pagina: James - Hartin, P. J. (Patrick J.) (Book collections on Project MUSE., 2009)
"The letter of James is one of the most neglected writings of the New Testament. One of the strongest and most influential voices against James has been that of Martin Luther who saw James as a challenge to Paul's teaching on the relationship between faith and works. Even within the Roman Catholic Church, James has suffered great neglect as is evidenced through the scant usage of this writing within her liturgy." "Hartin's study begins with a detailed examination of the letter's literary background and its relationships within the context of the Jewish, Hellenistic, and emerging Christian worlds. From this examination James emerges clearly as a writing at home within the world of Jewish-Christianity. Those complex issues of genre, authorship, and readership are examined, and Hartin argues convincingly that James is an early writing, stemming from the authority of James, the brother of the Lord, who writes to those Jewish-Christians in the dispersion of northern Syria."--Jacket.